Synthesis and Characterization of Stimuli-Responsive Poly (Maleic Acid-Co-Malic Acid-Co-Propane-1,2-Diol-Co-Adipic Acid) - Matin, Md. Abdul; Chowdhury, Monishita Nuzhat; Khatun, Anjuman Ara; Nasrin, Jahanara; Mahmud, Abu (European Journal of Applied Sciences, 2023)
Poly (Maleic acid-co-Malic acid-co-Propane-1,2-diol-co-Adipic acid) was synthesized using the Dean-Stark apparatus. Stoichometric proportions of maleic acid, malic acid, adipic acid and propane-1, 2-diol were taken in a round bottom flask along with a trace amount of anhydrous ferric chloride which worked as catalyst and o-xylene used as reaction medium. The total system was heated at temp. 135-1400C for about 5 hours. Molecular weight, FTIR-spectra, thermo gravimetric and elemental analysis, solubility tests in common organic solvents, melting point and degradation tests were used for the characterization of the synthesized co-polyester. At room temperature (300C) the hydrolytic degradation study of the co-polyester in solutions of various pH values (pH=1.15-4.40) showed that, there has no degradation of the co-polyester, but it gradually degraded in solutions of pH values 6.50-8.99. This showed its stimuli-responsive characteristics. The co-polyester almost 70% degraded in normal soil within 30 days indicating its biodegradable nature. If satisfactory toxicity result of the synthesized co-polyester is observed, it might be usable as an enteric coating material.